Karakteristik Peternak dan Usaha Ternak Ayam Petelur Desa Pesedahan, Kecamatan Manggis, Kabupaten Karangasem, Provinsi Bali (Jurnal Agribisnis dan Agrowisata, 2025)
Characteristics of Breeder and Livestock Business of Laying Hens in Pesedahan Village, Manggis District, Karangasem Regency, Bali Province. The business center for laying hens in Karangasem Regency is located in Pesedahan Village, Manggis District, Karangasem Regency. In this case the population of laying hens in Pesedahan Village occupies the largest number of laying hens in Karangasem Regency with a total of 350,150 laying hens and an average egg production of 150,000 eggs/day. So that through this promising potential, there is a need for urgency regarding a clear identification of the description of the breeder as the manager of the livestock business and what things need to be known regarding the management of the laying hen business in Pesedahan Village. The purpose of this study was to determine the characteristics of breeders and laying hens in Pesedahan Village. The analytical method used to analyze the characteristics of breeders and livestock businesses is a quantitative and qualitative descriptive method. Based on the analysis, the characteristics of laying hen breeders can be grouped based on the categories of gender, age, education and business experience. While the characteristics of the livestock business can be grouped based on the category of business pattern, source of capital, source of seeds, source of feed, marketing system, area of the stable, livestock population, number of egg production, and number of workers.
Keywords: laying hens